Effects of hydroxyethyl starch 130/0.4 on the kidney tissue of rats with ureteral obstruction - Güneş I; Süngü N; Kılıçarslan A; Şıvgın V; Alkan M; Küçük A; Boyunağa H; Ünal Y; Arslan M (Dove Medical Press, 2018)
Işın Güneş,1 Nuran Süngü,2 Aydan Kılıçarslan,2 Volkan Şıvgın,3 Metin Alkan,3 Ayşegül Küçük,4 Hakan Boyunağa,5 Yusuf Ünal,3 Mustafa Arslan3 1Department of Anaesthesiology and Reanimation, Erciyes University Medical Faculty, Kayseri, Turkey; 2Department of Pathology, Yıldırım Beyazıt University Medical Faculty, Ankara, Turkey; 3Department of Anaesthesiology and Reanimation, Gazi University Medical Faculty, Ankara, Turkey; 4Department of Physiology, Dumlupinar University Medical Faculty, Kütahya, Turkey; 5Department of Biochemistry, Kirikkale University Medical Faculty, Kirikkale, Turkey Objective: This study was conducted since the effects of colloid solutions on the renal system remain controversial and need to be adequately studied in animals. We aimed to evaluate the effects of hydroxyethyl starch (Voluven) on the kidney tissue of rats with late renal failure due to ureteral obstruction. Materials and methods: Rats were divided into four groups: Group C, control; Group HES, hydroxyethyl starch solution (HES) 130/0.4 (Voluven®); Group UUO, unilateral ureteral obstruction (UUO); and Group UUO-HES, UUO-HES 130/0.4 (Voluven®). In the groups with ureteral obstruction, the distal part of the right ureter was accessed and sutured through a lower abdominal incision under ketamine anesthesia. Any signs of late-stage renal failure were evaluated after three weeks. Rats in the HES group and the renal failure-HES group were administered with HES 130/0.4 as a single intravenous dose of 20 mL/kg. After a follow-up of 24 hours, intra-abdominal blood sample was collected, and the rats were sacrificed. Biochemical and histopathological parameters were then evaluated. Results: Ureteral obstruction significantly increased urea and creatinine levels. In addition, when the UUO-HES and HES groups were compared, the administration of HES increased urea and creatinine levels in the UUO-HES group. Nitric oxide enzyme activity and malondialdehyde levels have significantly increased in the UUO groups. In addition, HES significantly increased nitric oxide activity and malondialdehyde levels in the UUO-HES group, in comparison with the HES group. The activity of caspases 3 and 8 was significantly increased in the UUO groups. In addition, HES significantly increased the activity of caspases 3 and 8 in the UUO-HES group, in comparison with the HES group. Light microscopy revealed significant changes in the UUO groups, especially in the obstructed kidneys. Conclusion: If indicated, HES should be used with caution in cases of UUO, but not in the cases of bilateral ureteral obstruction. Other aspects of these findings, including the clinical significance and practical applications, merit further experimental and clinical investigation. Keywords: unilateral ureteral obstruction, hydroxyethyl starch solution 130/0.4, caspase 3, caspase 8, malondialdehyde, nitric oxide